Music listening evokes story-like visual imagery with both idiosyncratic and shared content. - Sarah Hashim; Lauren Stewart; Mats B Küssner; Diana Omigie (PLoS ONE)
There is growing evidence that music can induce a wide range of visual imagery. To date, however, there have been few thorough investigations into the specific content of music-induced visual imagery, and whether listeners exhibit consistency within themselves and with one another regarding their visual imagery content. We recruited an online sample (N = 353) who listened to three orchestral film music excerpts representing happy, tender, and fearful emotions. For each excerpt, listeners rated how much visual imagery they were experiencing and how vivid it was, their liking of and felt emotional intensity in response to the excerpt, and, finally, described the content of any visual imagery they may have been experiencing. Further, they completed items assessing a number of individual differences including musical training and general visual imagery ability. Of the initial sample, 254 respondents completed the survey again three weeks later. A thematic analysis of the content descriptions revealed three higher-order themes of prominent visual imagery experiences: Storytelling (imagined locations, characters, actions, etc.), Associations (emotional experiences, abstract thoughts, and memories), and References (origins of the visual imagery, e.g., film and TV). Although listeners demonstrated relatively low visual imagery consistency with each other, levels were higher when considering visual imagery content within individuals across timepoints. Our findings corroborate past literature regarding music's capacity to encourage narrative engagement. It, however, extends it (a) to show that such engagement is highly visual and contains other types of imagery to a lesser extent, (b) to indicate the idiosyncratic tendencies of listeners' imagery consistency, and (c) to reveal key factors influencing consistency levels (e.g., vividness of visual imagery and emotional intensity ratings in response to music). Further implications are discussed in relation to visual imagery's purported involvement in music-induced emotions and aesthetic appeal.